Strategies of Epstein-Barr virus to evade innate antiviral immunity of its human host - Albanese, Manuel; Tagawa, Takanobu; Hammerschmidt, Wolfgang (Frontiers in Microbiology, 2022)
Epstein-Barr virus (EBV) is a double-stranded DNA virus of the Herpesviridae family. This virus preferentially infects human primary B cells and persists in the human B cell compartment for a lifetime. Latent EBV infection can lead to the development of different types of lymphomas as well as carcinomas such as nasopharyngeal and gastric carcinoma in immunocompetent and immunocompromised patients. The early phase of viral infection is crucial for EBV to establish latency, but different viral components are sensed by cellular sensors called pattern recognition receptors (PRRs) as the first line of host defense. The efficacy of innate immunity, in particular the interferon-mediated response, is critical to control viral infection initially and to trigger a broad spectrum of specific adaptive immune responses against EBV later. Despite these restrictions, the virus has developed various strategies to evade the immune reaction of its host and to establish its lifelong latency. In its different phases of infection, EBV expresses up to 44 different viral miRNAs. Some act as viral immunoevasins because they have been shown to counteract innate as well as adaptive immune responses. Similarly, certain virally encoded proteins also control antiviral immunity. In this review, we discuss how the virus governs innate immune responses of its host and exploits them to its advantage.